Bookmarks are people too! - Winkler, Henry, 1945-; Oliver, Lin (Winkler, Henry, 1945- Here's Hank ;, 2014)
Hoping to land the lead in the class play, Hank freezes during his audition and is only able to buzz like a fly, inspiring his teacher to create a special role for him as a silent bookmark that saves the show when a rival suffers an attack of stage fright.